Zonation of benthic macrofauna on Cassino Beach, southernmost Brazil (Brazilian Journal of Oceanography, 2007)
Benthic macrofauna zonation was studied for one year (June 2004 to May 2005) with monthly sampling on Cassino Beach, Rio Grande do Sul, Brazil. Three sites (spaced 50 m apart) were selected. Three transects were anchored at each site, spaced equidistantly 2 m apart. Each transect extended from the base of the primary dunes to the inner surf zone at approximately 1m in depth, with between 7 and 8 sampling levels. Monthly, with a 20 cm diameter core, one biological sample was collected per transect at each level, a total of nine samples per level. Within transects, the distance between the levels was 20 m until the upper swash zone, from which the distance was 10 m until the 1-meter isobath. Zonation proved to be variable throughout the year. Variability was mainly a reflection of the greater instability of the lower part of the beach, which comprised the lower mesolittoral zone and the inner surf zone. This was evidenced seasonally with the formation of distinct groups of fauna in accordance with the peculiarity of each season of the year. The formation of these groups was strongly influenced by fluctuations in densities stemming from recruitments and the migration of juvenile and adult infauna, as well as superimposing of the distribution of organisms as a result of rises in sea level due to storms.